Retailer volunteerism as a plastic shopping bag governance tool: shoppers’ reflections and contributions to environmental social marketing - Muposhi, Asphat; Shamhuyenhanzva, Roy (SAGE Publications, 2022)
Introduction The pollution of landscapes and coastal environments with plastic shopping bag litter is an escalating global problem. The introduction of plastic bag tax aimed at addressing this challenge achieved limited success in South Africa. This study explores South African shoppers’ perceptions towards social marketing anchored retailer voluntary initiatives, which is an emerging plastic bag policy option.